1985
DOI: 10.1159/000180036
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitor of Urokinase and Tissue Plasminogen Activators in Dunning R3327H Prostate Tumors of Rats Treated with <i>D</i><i>-</i>Trp<sup>6</sup>-LH-RH

Abstract: The antifibrinolytic activity of cytosol from Dunning R3327H rat prostate tumors was studied. The prostate tumors from rats treated with D-Trp6-LH-RH had 2.5 times lower plasminogen activator activity than tumors from untreated rats. This was due to the presence of an inhibitor of plasminogen activator as well as a reduction in residual activity of plasminogen activator(s). Only the cytosolic extracts from prostate tumors of rats treated with D-Trp6-LH-RH contained this inhibitor. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The PAI synthesized by cultured rat granulosa cells is also immunologically related to the BAE PAI (40), suggesting that this class ofPAIs may regulate a variety of processes involving plasminogen activation. The relationship of these PAIs to the PAIs elaborated by macrophages (37), uterine cells (41), and tumor cells (42) remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The PAI synthesized by cultured rat granulosa cells is also immunologically related to the BAE PAI (40), suggesting that this class ofPAIs may regulate a variety of processes involving plasminogen activation. The relationship of these PAIs to the PAIs elaborated by macrophages (37), uterine cells (41), and tumor cells (42) remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Both urokinase and tissuetype activator are expressed in the PA-I11 tumor cell line from Lobund-Wistar rats (Strickland et al, 1983) and in the spontaneous tumors found in the ventral prostate of aged Fisher-344 rats . Treatment of rats bearing Dunning R3327H tumors with D-trp'-LH-RH decreases tumor volume and tumor plasminogen activator activities; the latter are blocked by a 21 kDa inhibitor that is induced in the tumor by this treatment (Hierowski and Schally, 1985). Thus, there is also a strong correlation of increased plasminogen activator activities with prostatic tumors in the rat.…”
Section: Proteases In Prostate Diseasementioning
confidence: 91%
“…Using these cell lines it was demonstrated that various biochemical markers for metastatic phenotypes, such as Ecadherin, differed in the sublines [23][24][25]. Elevated levels of plasminogen activator [26], and of MMP-2 and MMP-9 [16], were found in the Dunning rat prostate tumor when compared with the dorsal prostate, which is considered the tissue source of the original tumor [21]. Although Lowe and Isaacs [23] did not detect any difference in plasminogen activator or matrix metalloproteinase activities in variants of the Dunning tumor cell lines, inhibition of u-PA activity was shown to decrease tumor volume [26].…”
Section: Introductionmentioning
confidence: 99%